2021
DOI: 10.3390/jcm10173819
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications of Resveratrol in Hepatic Encephalopathy through Its Regulation of the Microbiota, Brain Edema, and Inflammation

Abstract: Hepatic encephalopathy is a common complication in patients with liver cirrhosis and portosystemic shunting. Patients with hepatic encephalopathy present a variety of clinical features, including neuropsychiatric manifestations, cognitive dysfunction, impaired gut barrier function, hyperammonemia, and chronic neuroinflammation. These pathogeneses have been linked to various factors, including ammonia-induced oxidative stress, neuronal cell death, alterations in the gut microbiome, astrocyte swelling, and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 158 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, resveratrol exhibited pronounced antioxidant potential in several models, principally via the control of major antioxidant enzymes, and block of DNA damage by free radicals (Pal and Sarkar 2014 ; Szkudelski and Szkudelska 2018 ; Meng et al 2021 ). Former investigations demonstrated that it could also decrease the level of 8-OHdG, suppress NOx production, and reverse the disruption of energy homeostasis by elevating the production of ATP in cellular mitochondria (Saleh et al 2017b ; Ahmed et al 2020 ; Meng et al 2021 ; Kim and Song 2021 ). Furthermore, in-vitro and in-vivo studies delineated the ability of resveratrol to improve liver functions represented by declination in ALT and AST levels, reduction of ammonia levels, maintenance of the blood-brain barrier (BBB) integrity, amelioration of hyperammonemia-induced mitochondrial dysfunction, and disruption in the glutamatergic system and cellular redox imbalance (Bobermin et al 2015 , 2018 ; Vairappan et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, resveratrol exhibited pronounced antioxidant potential in several models, principally via the control of major antioxidant enzymes, and block of DNA damage by free radicals (Pal and Sarkar 2014 ; Szkudelski and Szkudelska 2018 ; Meng et al 2021 ). Former investigations demonstrated that it could also decrease the level of 8-OHdG, suppress NOx production, and reverse the disruption of energy homeostasis by elevating the production of ATP in cellular mitochondria (Saleh et al 2017b ; Ahmed et al 2020 ; Meng et al 2021 ; Kim and Song 2021 ). Furthermore, in-vitro and in-vivo studies delineated the ability of resveratrol to improve liver functions represented by declination in ALT and AST levels, reduction of ammonia levels, maintenance of the blood-brain barrier (BBB) integrity, amelioration of hyperammonemia-induced mitochondrial dysfunction, and disruption in the glutamatergic system and cellular redox imbalance (Bobermin et al 2015 , 2018 ; Vairappan et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, resveratrol is a natural polyphenolic compound that exhibits beneficial pharmacological properties in a wide range of brain abnormalities; acting mainly as a neuroprotective with monoamines-preserving potential. It was reported to exhibit protective effects against many neurodegenerative diseases (Aguirre et al 2014 ; Martínez-Abundis et al 2016 ; Ahmed et al 2020 ), and it was particularly shown to prevent ammonia toxicity by modulating oxidative stress (Malaguarnera et al 2018 ; Kim and Song 2021 ). Moreover, it was reported that resveratrol exhibited neuroprotective effect against glutamate toxicity (Quincozes-Santos et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these results may shed some light on a better understanding of the gut-liver axis and liver functional changes in bedridden patients. It also urges the development of nutritional or pharmacological countermeasures 84,85 to improve the gut-liver axis and metabolic functions in astronauts and bedridden people.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have hypothesized that resveratrol plays a pleiotropic role in reducing liver fibrosis by inhibiting stellate cells, reducing oxidative stress, lipid peroxidation and iron overload, improving hepatic glucose metabolism and insulin activity and inducing hepatic cancer cells apoptosis in different in vitro and in vivo models. In addition, other interesting data suggest that resveratrol may prevent brain edema and neuroinflammation by protecting the blood-brain barrier and facilitating the maintenance of its integrity, with a therapeutic potential in hepatic encephalopathy, mainly through gut microbiome modulation [260]. Limited data from human-based studies reveal that resveratrol improves blood pressure, waist circumference, insulin sensitivity and fasting glucose levels in patients with type 2 diabetes mellitus and may improve inflammatory status in individuals with obesity [261].…”
Section: Carnitinementioning
confidence: 99%